Complete MBA companion (Financial Times, 1997)
Although this book originally appeared as a 20-part weekly supplement to the UK edition of the Financial Times, it has been organized here to resemble a textbook. Its contributors number nearly 100 academicians, and it is based on the core curricula of three of the world's most prestigious business schools: Wharton, London Business School, and IMD of Lausanne, Switzerland. Nonetheless, the 20 individual chapters (or modules) have been combined into a coherent, readable whole that both lays out the current philosophies and summarizes recent trends and developments in the fields of accounting, finance, marketing, human resources, business ethics, leadership, etc. Quite suitable for basic, general, and academic collections.